Indians of the Pacific Northwest - Liptak, Karen (New York : Facts on File, 1991)
Examines the history, culture, changing fortunes, and current situation of the various groups of Indians living in the Pacific Northwest
Includes index
Keywords: Indians of North America -- Northwest Coast of North America -- Juvenile literature